PENGARUH HARGA DAN VARIASI PRODUK TERHADAP LOYALITAS KONSUMEN DENGAN LINGKUNGAN USAHA SEBAGAI VARIABEL MODERATING (Studi Pada Usaha Perorangan Toko Rahma Muslimah Hijab dan Syar’i) - Afia Rohmatul, Vivi Afia Rohmatul; Wahyuni, Ika; Subaida, Ida (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The aim of this research is to analyze the influenceThe Influence of Service The purpose of this study is to analyze the influence of variables Influence Price and Product Variation on Consumer Loyalty with Business Environment as a Moderating Variable (Study on Individual Business "Toko Rahma Muslimah Hijab and Syar'i)". Using the Partial Least Square (PLS) Structural Equation Model. Results of direct influence hypothesis testing using the Smart PLS 3.0 application Price has a significant positive effect on customer loyalty (H1 is accepted), Product variation has a significant positive effect on customer loyalty (H2 is accepted), Business environment is positive but not significant as a moderating variable for the influence of price on customer loyalty (H3 is rejected), and Business environment is positive but not significant as a moderating variable for the influence of product variation on customer loyalty (H4 is rejected).